Nordic Food in Japan : Market Potential and Brand Image - Heikura, Tuomo (Oulun ammattikorkeakoulu, 2018)
This bachelor’s thesis examines the market potential and brand of Nordic food and berries in Japan and has been produced as a part of the Arctic Berry Wax Project which is a cooperation between multiple different Nordic universities. The primary goal of the Arctic Berry Wax Project is to produce environmentally sustainable methods to extract wax from arctic berries by using industrial side streams and waste as a base. One goal of the project is also to find out applications to use the wax in different industries and create potential wax-based products. In this project, Oulu University of Applied Sciences is researching different usages for the wax in products and finding information regarding potential market areas for the wax-based products as well as collaborating with potential business partners. This thesis aims to study the current food industry market potential in Japan for Nordic based food products as well as researching the brand image of Nordic countries and food in the eyes of Japanese people. The theoretical framework of this thesis is built around background information regarding political, cultural and trade relationships between Japan and Nordic countries as well as information regarding the food and beverage market in Japan. There is also a chapter regarding the branding theory in the form of nation branding as well as food branding theory. The empirical part of this thesis was conducted in a qualitative manner, in the form of an interview and a questionnaire. The interview’s aim was to research the market potential of Japan, and the questionnaire aimed to collect information regarding the brand image of Nordic countries and food. On the basis of the results, Japan indeed offers opportunities for Nordic food companies. Nordic countries also have a positive image in Japan currently which should definitely be used by Nordic companies when they start marketing their products in Japan. Entering the Japanese market can be a challenging task for Nordic companies because of the cultural and language ...